SIRT5 Contributes to Colorectal Cancer Growth by Regulating T Cell Activity - Ke Wang; Zuojian Hu; Cuiping Zhang; Lujie Yang; Li Feng; Pengyuan Yang; Hongxiu Yu (Journal of Immunology Research)
Over the past several years, SIRT5 has attracted considerable attention in metabolic regulation. However, the function of SIRT5 in tumorigenesis by regulating tumor microenvironment is poorly understood. In this work, we found that Sirt5 knockout mice were resistant to AOM and DSS-induced colitis-associated colorectal tumorigenesis and the level of IFN-γ in their tumor microenvironment was higher. Additionally, proteome and network analysis revealed that SIRT5 was important in the T cell receptor signaling pathway. Furthermore, we determined that a deficiency of Sirt5 induced stronger T cell activation and demonstrated that SIRT5 played a pivotal role in regulating the differentiation of CD4+ regulatory T (Treg) cells and T helper 1 (Th1) cells. An imbalance in the lineages of immunosuppressive Treg cells and the inflammatory Th1 subsets of helper T cells leads to the development of colon cancer. Our results revealed a regulatory role of SIRT5 in T cell activation and colorectal tumorigenesis.